Deterministic Fabrication of Fluorescent Nanostructures Featuring Distinct Optical Transitions - Marijn Rikers; Ayesheh Bashiri; Ángela Barreda; Michael Steinert; Duk-Yong Choi; Thomas Pertsch; Isabelle Staude (Nanomaterials)
The precise and deterministic integration of fluorescent emitters with photonic nanostructures is an important challenge in nanophotonics and key to the realization of hybrid photonic systems, supporting effects such as emission enhancement, directional emission, and strong coupling. Such integration typically requires the definition or immobilization of the emitters at defined positions with nanoscale precision. While various methods were already developed for creating localized emitters, in this work we present a new method for the deterministic fabrication of fluorescent nanostructures featuring well-defined optical transitions; it works with a minimal amount of steps and is scalable. Specifically, electron-beam lithography is used to directly pattern a mixture of the negative-tone electron-beam resist with the europium complex Eu(TTA)3, which exhibits both electric and magnetic dipolar transitions. Crucially, the lithography process enables precise control over the shape and position of the resulting fluorescent structures with a feature size of approx. 100 <semantics>n</semantics><semantics>m</semantics>. We demonstrate that the Eu(TTA)3 remains fluorescent after exposure, confirming that the electron beam does not alter the structure the optical transitions. This work supports the experimental study of local density of optical states in nanophotonics. It also expands the knowledge base of fluorescent polymer materials, which can have applications in polymer-based photonic devices. Altogether, the presented fabrication method opens the door for the realization of hybrid nanophotonic systems incorporating fluorescent emitters for light-emitting dielectric metasurfaces.